PERILAKU PEMBERIAN ASI TERHADAP FREKUENSI DIARE PADA ANAK USIA 6-24 BULAN DI RUANG ANAK RUMAH SAKIT BAPTIS KEDIRI - Febrijanto, Yoyok; Romoekoij, Stefanny Puput; Victoria, Fitri Suli (Jurnal Penelitian STIKES Kediri, 2011)
abstract   backgorund : Breast feeding or ASI in Indonesia a magical and uncomparable liquid. This main nutrition is needed by newly born baby. The problem accurs when a mother decides to stop breast feeding to the newly born baby due to some reasons. The first reason is a myth that breast feeding is not sufficient in fulfilling baby’s needed. The second reason is career. Eventhought breast feeding is very beneficial, mother’s outside who work prefer to give up in breast feeding. Method : The design of study was correlational analytic.The populations were children 6 to 24 months that suffer diarrhea in Pediatric ward of Kediri Baptist Hospital. The sample were 38 respondents.These were taken using total sampling. The independent variable was breast feeding. The dependent variabel was diarrhea episode. The data were collected using checklist. The data were  analyzed using pearson with level of significance 0.05. Conclusion : The statistics test result showed correlation between diarrhea episode and breast feeding on child of age 6 to 24 months in Pediatric ward of Kediri Baptist Hospital (p = 0.000). It could be concluded that breast feeding has correlation with diarrhea episode on child of age 6 to 24 months in Pediatric ward of Kediri Baptist